2021
DOI: 10.1111/ajd.13596
|View full text |Cite
|
Sign up to set email alerts
|

Teledermatology in a rural area of southern Spain: A 12‐year study

Abstract: Nonredundant roles of Interleukin-17A (IL-17A) and IL-22 in murine host defense against cutaneous and hematogenous infection due to methicillin-resistant Staphylococcus aureus. Infect. Immun. 2015; 83: 4427-37. 4. Das S, Khader S. Yin and yang of interleukin-17 in host immunity to infection. F1000Res. 2017; 23(6): 741. 5. Zhang L, Yang H, Chen Q et al. Adverse drug events observed with 150 mg versus 300 Mg secukinumab for the treatment of moderate to severe plaque psoriasis: a systematic review and meta-analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
1
1
0
Order By: Relevance
“…Another study in Brazil found that TD allowed two-thirds of patients to avoid in-person visits [ 34 ]. Similar values were found in rural Spain, where a TD program saved patients and providers 1496 working hours, 786 travel hours, 8280 dollars, and 51.3 km in distance traveled [ 35 ]. In addition, large-scale, cost-effectiveness analyses have pointed to the extensive societal savings TD can bring to areas with limited dermatologic care [ 36 , 37 ].…”
Section: Effectiveness and Benefits: Teledermatology For Global Under...supporting
confidence: 67%
“…Another study in Brazil found that TD allowed two-thirds of patients to avoid in-person visits [ 34 ]. Similar values were found in rural Spain, where a TD program saved patients and providers 1496 working hours, 786 travel hours, 8280 dollars, and 51.3 km in distance traveled [ 35 ]. In addition, large-scale, cost-effectiveness analyses have pointed to the extensive societal savings TD can bring to areas with limited dermatologic care [ 36 , 37 ].…”
Section: Effectiveness and Benefits: Teledermatology For Global Under...supporting
confidence: 67%
“…IL-17 has important roles in immune surveillance against various microorganisms. 4,10,11 We and others have observed dermatophyte infections, implicating superficial fungal infections to be an underestimated adverse effect of IL-17 antagonists.…”
Section: Discussionmentioning
confidence: 94%